The Pilates breathing technique increases the electromyographic amplitude level of the deep abdominal muscles in untrained people. - Barbosa, Alexandre Wesley Carvalho; Guedes, Camila Antunes; Bonifácio, Douglas Novaes; de Fátima Silva, Angélica; Martins, Fábio Luiz Mendonça; Almeida Barbosa, Michelle Cristina Sales (Journal of Bodywork & Movement Therapies, 2015)
Summary Objective To evaluate the behaviour of the upper rectus abdominis , lower rectus abdominis and transverse abdominis/internal oblique (TrA/IO) by using surface electromyography during trunk flexion with and without the Pilates breathing technique. Methods Nineteen female subjects (without experience of the Pilates method) were recruited. The muscles were evaluated while trunk flexion was performed by using the Pilates breathing technique (POW) and Step Barrel device, followed by another contraction without the technique (NORM). Normality was accepted, and the paired t -test was used to determine data differences ( p < 0.05). Results Significant differences were noted in the amplitude level of activation between TrA/IO-POW and TrA/IO-NORM. The activation amplitude level of TrA/IO-POW significantly increased compared with all the other muscles under the NORM condition. Conclusion The breathing technique of the Pilates method associated with trunk flexion increases TrA/IO electrical activity.